PERLINDUNGAN HUKUM TERHADAP PIHAK YANG LEMAH DALAM PENGGABUNGAN PERUSAHAAN (MERGER) - Essa Santhira Dalem, Cok Istri; Sukerti, Ni Nyoman (Kertha Semaya : Journal Ilmu Hukum, 2013)
That the Company Law has provided protection to the weak, as well as the implementing regulations, which can be differentiated into structural protection, financial systems and the silent majority super majority, and the protection of the localization system;That the Company Law has also been applying the principles of appraisal rights, as one a form of protection to the weaker party in a merger, the contained in Article 102 in conjunction with the Company Law 123.
Keywords: Legal Protection, The Weak, The Incorporation Of The Company